The role of early age structural build-up in digital fabrication with concrete. (October 2018) - Reiter, Lex; Wangler, Timothy; Roussel, Nicolas; Flatt, Robert J.
Abstract: The advent of digital fabrication for concrete calls for advancing our understanding of the entanglement of processing technology, rheology, admixture use and hydration control, in addition to developing novel measurement and control techniques. We provide an overview of recently proposed building processes, defining the type and range of yield stress evolution that they require for successful building. In doing so, we explain which mechanisms are at stake and how their consequences can be measured. Controlling the structural build-up of concrete with the precision required by digital processes will be at the heart of future progress. For this, chemically controlling cement hydration of concrete is essential and we provide an overview of admixtures, focusing on "set on demand" solutions, concluding that activators should be added as closely to the delivery point as possible. Advantages and limitations are discussed and showcased using recent successes in process scaling and material and process control.